Pengaruh Kompensasi Dan Kepuasan Kerja Terhadap Kinerja Karyawan Toko Buku Togamas Solo(Studi Kasus Pada Karyawan Toko Buku Togamas Solo) - Aryaningtyas, Ayu, Drs. Ma'ruf, MM (2017)
This study aim to determine the effect of compensation and job satisfaction on job performance of Toko Buku Togamas Solo. Samples taken in this study were employees of Toko Buku Togamas Solo. Distributing questionnaires to 39 respondents Toko Buku Togamas Solo taken by census sampling. Data analysis methods used are validity, reliability test,the analysis of the classical assumptions and test multiple linear regression analysis with t-test, F and coefficient of determination (R2). Hypothesis tests showed the effect of compensation and job satisfaction have significant influence with t respectively 3,285 and 2,918. In the F test showed that together the variable compensation and job satisfaction significantly influence on job performance with a probability value of 0.000 (0.000 <0.05). And the coefficient of determination (R2) of 54.8%.